1973: Chilean academics in the Emergency - Bayle, Paola (Österreichische Zeitschrift für Geschichtswissenschaften, 2010)
Following the military coup d’état on 11 September 1973, the Chilean academic field went through a significant process of reconfiguration as thousands of students, teachers and researchers were excluded, numerous centres of study were closed, and areas of research and careers were terminated. In response, expressions of solidarity multiplied around the world. In the United Kingdom, British academics – mainly those involved in Latin American studies and development studies – were the first to get organized under the name Academics for Chile, in order to support their Chilean peers affected by the military coup. These endeavours were channelled through a programme of scholarships managed by the World University Service, United Kingdom (WUS UK). The paper focuses on that Scholarship Programme for Chilean Refugees. This programme is described as an experience born where British academia and the political world intersected. I propose a trans-national view of the phenomenon of exile that highlights particular nexuses – academic links, and political and social networks – between different national communities.